(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The research aimed study the children with attention-deficit/hyperactivity disorder (ADHD) more likely Creates to irritable bowel syndrome at Ibn-Rushd Psychiatric Teaching Hospital in Baghdad city, find out the relationship between demographic characteristic, irritable bowel syndrome and Attention-Deficit/ Hyperactivity disorder patients. A purposive (non-probability), the sample included (100) patients, from (3-11) years old. A descriptive study carried out from December 10th 2018 to the February 25th 2019, from family Attention-Deficit/Hyperactivity Disorder outpatients of Ibn-Rushd Psychiatric Teaching Hospital in Baghdad city. A questionnaire was constructed for the purpose of the study, which was a consisted of (2) part. The 1st part included the demographic characteristics and the 2nd part included the items related with irritable bowel syndrome. Data were analyzed through descriptive statistical approach (frequency and percentage) and inferential statistical approach (correlation coefficient). Scores, Perpson, lycart scale analysis that include, t-test, and stepwise multiple regression. The result of the study confirmed that the mean of score for the age of sample was (7.1) year, most of them male urban, low score for socio-economic status, strong positive to irritable bowel syndrome.